PENINGKATAN PENGETAHUAN DAN KETERAMPILAN KADER MELALUI PELATIHAN TENTANG PRAKTIK DALAM PEMBERIAN MAKAN PADA BALITA DALAM UPAYA PENCEGAHAN DAN MENURUNKAN KEJADIAN STUNTING - lince amelia; Indah Dwi Rahayu; Dinarwulan Puspita; Ditha Astuti Purnamawati (Jurnal Pengabdian Masyarakat, 2023)
Nutritional problems in children under five are influenced by food intake and infectious diseases. Lack of vitamins that make children experience growth disorders, can cause growth disorders, and nutritional problems in toddlers are stunting. The stunting rate of children under five in Indonesia is still high and is a health problem that must be addressed. Efforts to prevent and control stunting are still being carried out, one of which is by increasing the knowledge of cadres about feeding practices to toddlers. Posyandu cadres are community members who are chosen from and by the community. The purpose of this PKM is to increase the knowledge of cadres skills about feeding practices to toddlers and the output targets to be achieved are published online media and journal articles. This community service method is health education about feeding toddlers and mentoring in practicing feeding toddlers. Participants in this community service are posyandu cadres as many as 12 people. The place for community service is at the Posyandu, Pal IX Village, Sungai Kakap District, Kubu Raya Regency. After providing health education and training in practicing how to feed toddlers, the posyandu cadres understand how to feed toddlers and the introduction of food textures at every age.